Effective interpersonal skills: embracing prophetic teachings - Wan Yusoff, Wan Mazwati (2020)
This module aims at raising awareness of our daily habits of communication and the need to change the wrong and reinforce the right habits especially the words that we use in communicating. Word is so powerful that it can change one's emotion in a split second. Words significantly influences behaviour. Therefore, continuously bombarding someone with wrong kind of words would reinforce undesirable behaviour. Prophet Muhammad is an epitome of a man with perfect moral behaviour which means that all aspects of his life are for us to emulate. Many have written about the Prophet as a leader, husband, father, commander, and so an but rarely we found literature that explicates the Prophet as an excellent communicator. This module will train participants in communicating using Prophet Muhammad's methods.